2021
DOI: 10.1002/ehf2.13184
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteoglycan prolargin in diagnosis and differentiation of pulmonary arterial hypertension

Abstract: Aims Right ventricular dysfunction may arise because of pulmonary arterial hypertension (PAH). Development of new diagnostic methods able to identify PAH and allow for earlier treatment initiation, before the development of vascular remodelling and manifest right heart failure (HF), could potentially improve prognosis. Proteoglycans and inflammatory proteins are involved in vascular remodelling. We aimed to investigate their potential as biomarkers to differentiate PAH in a dyspnoeic population. Methods and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In the present PAH cohort, glypican‐1 levels at follow‐up were increased compared to baseline. This indicates that the change in glypican‐1 levels may be related to PAH‐specific treatment, as we previously have found glypican‐1 levels to be decreased at PAH diagnosis compared to healthy individuals 14 . Glypican‐1 is a mediator of flow‐induced endothelial nitric oxide synthase activation 32 .…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In the present PAH cohort, glypican‐1 levels at follow‐up were increased compared to baseline. This indicates that the change in glypican‐1 levels may be related to PAH‐specific treatment, as we previously have found glypican‐1 levels to be decreased at PAH diagnosis compared to healthy individuals 14 . Glypican‐1 is a mediator of flow‐induced endothelial nitric oxide synthase activation 32 .…”
Section: Discussionmentioning
confidence: 69%
“…Consequently, ECM proteins could be of interest as prognostic markers in PAH. The present study, therefore, investigated ECM‐related proteins that we previously had found to be altered in the plasma of patients with PAH compared to healthy controls 13,14 . Among the ECM proteins evaluated in the present study, MMP‐2 was the most promising prognostic marker of outcome in PAH.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations